2017
DOI: 10.2741/4479
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial nucleic acid binding proteins associated with diseases

Abstract: Mammalian mitochondrial DNA (mtDNA) exists in structures called nucleoids, which correspond to the configuration of nuclear DNA. Mitochondrial transcription factor A (TFAM), first cloned as an mtDNA transcription factor, is critical for packaging and maintaining mtDNA. To investigate functional aspects of TFAM, we identified many RNA-binding proteins as candidate TFAM interactors, including ERAL1 and p32. In this review, we first describe the functions of TFAM, replication proteins such as polymerase gamma and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…As a first key finding, ClpP pathogenic variants trigger the protein accumulation of POLDIP2, LRPPRC, and GFM1 with high consistency between mammalian species and cell types. While POLDIP2 functions at the nucleoid and LRPPRC at the mitochondrial RNA granule modulating polyadenylation [ 41 , 42 , 65 , 66 ], GFM1 directly acts at mitoribosomes, and its excess was shown to impair translation [ 44 , 67 , 68 ]. Mitoribosomal dysfunction is considered a crucial site of pathology in Perrault syndrome, and these events occur upstream.…”
Section: Discussionmentioning
confidence: 99%
“…As a first key finding, ClpP pathogenic variants trigger the protein accumulation of POLDIP2, LRPPRC, and GFM1 with high consistency between mammalian species and cell types. While POLDIP2 functions at the nucleoid and LRPPRC at the mitochondrial RNA granule modulating polyadenylation [ 41 , 42 , 65 , 66 ], GFM1 directly acts at mitoribosomes, and its excess was shown to impair translation [ 44 , 67 , 68 ]. Mitoribosomal dysfunction is considered a crucial site of pathology in Perrault syndrome, and these events occur upstream.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that C1QBP is critical for mitochondrial biosynthesis, metabolism, and functional maintenance. C1QBP is involved in mitochondrial genome replication and regulates the activity of mitochondrial transcription factor A (TFAM), a key factor in packaging and maintaining mtDNA [55]. RECQ4 is a helicase involved in mt-DNA synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…As a first key finding, ClpP pathogenic variants trigger the protein accumulation of POLDIP2, LRPPRC and GFM1 with high consistency between mammalian species and cell types. While POLDIP2 functions at the nucleoid and LRPPRC at the mitochondrial RNA granule modulating polyadenylation [40,41,63,64], GFM1 directly acts at mitoribosomes and its excess was shown to impair translation [43,65,66]. Mitoribosomal dysfunction is considered a crucial site of pathology in Perrault syndrome, and these events occur upstream.…”
Section: Discussionmentioning
confidence: 99%